2012
DOI: 10.1508/cytologia.77.141
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Nucleolar Organizer Regions (NORs) of 4 Gibbon Species in Thailand by Ag-NOR Banding Technique

Abstract: Summary Localization of nucleolar organizer regions (NORs) of four gibbon species in Thailand was studied. Blood samples were taken from 1 male each of the following 3 species: white-handed gibbon (Hylobates lar), pileated gibbon (H. pileatus), and white-cheeked gibbon (Nomascus leucogenys): and 1 female of the dark-handed gibbon (H. agilis). These were subjected to standard whole blood T-lymphocyte culture. The samples were harvested by colchicine-hypotonic-fixation-air-drying technique and were followed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In addition, Nie et al (1998) found heteromorphic NOR of Phayre s langur (T. phayrei) and Francois langur (T. francoisi) on pair 21. The polymorphic NOR of Asian non-human primate was found in few species, for example white-handed gibbon (Hylobates lar), dark-handed gibbon (H. agilis), and moloch gibbon (H. moloch) (Warburton et al 1975, Tuinen et al 1999, Khunsook et al 2008, Tanomtong et al 2008a, 2008b, 2009, 2010, Supanuam et al 2012. A pattern of horizontal bright and dark bands on GTG-banding of Indochinese silvered langur, the number of banding pattern on a set of haploid number (n) including autosomes and sexchromosomes is 245 bands on metaphase and 301 bands on prometaphase chromosomes (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Nie et al (1998) found heteromorphic NOR of Phayre s langur (T. phayrei) and Francois langur (T. francoisi) on pair 21. The polymorphic NOR of Asian non-human primate was found in few species, for example white-handed gibbon (Hylobates lar), dark-handed gibbon (H. agilis), and moloch gibbon (H. moloch) (Warburton et al 1975, Tuinen et al 1999, Khunsook et al 2008, Tanomtong et al 2008a, 2008b, 2009, 2010, Supanuam et al 2012. A pattern of horizontal bright and dark bands on GTG-banding of Indochinese silvered langur, the number of banding pattern on a set of haploid number (n) including autosomes and sexchromosomes is 245 bands on metaphase and 301 bands on prometaphase chromosomes (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Argentophilic decondensed regions in vertebrates are often related to NOR sites ( Árnason 1981 ; Schmid et al 1982 ; Birstein 1984 ; Supanuam et al 2012 ). Previ ous cytogenetic studies identified an intriguing chromosomal region on homeologous pairs in B.…”
Section: Discussionmentioning
confidence: 99%
“…The white-cheeked gibbon (Nomascus leucogenys) is critically endangered (CR), (i.e., has an extremely high risk of extinction in the wild). Professor Tanomtong and his coworkers have analyzed the standardized karyotypes of these Thai gibbon species (Supanuam et al 2012), recommending the designation of 1 CR, 11 EN, and 12 vulnerable (VU) species (having a high risk of endangerment in the wild), and 7 nearthreatened (NT) species (likely to become endangered in the near future). The NT category includes the Sumatra serow, Capricornis sumatraensis (Jantarat et al 2017b), and Indian hog deer, Hyelaphus porcinus (Pinthong et al 2017a).…”
Section: Thailand Including the Indochina And Northern Malay Peninsulasmentioning
confidence: 99%